2021
DOI: 10.54207/bsmps1000-2021-dw8zer
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes and Corrections in the Taxonomy of Indian Pteridophytes: Part 2

Abstract: Taxonomic novelties and corrections to Indian Pteridophytes are given briefly here in taxonomic order according to the forthcoming Annotated Checklist of Indian Pteridophytes vol. 3, nearing completion for January 2021. We have divided it into two parts, the present second part is from the Appendix re corrections and additions to Families treated in vols. 1-2, especially concerning relevant publications that appeared subsequently to the two volumes. Further details of the taxa and references are given in vol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Kuo and T. subsageniacea (Christ) Christenh. ( Holttum 1988 ; Kuo 1997 ; Zink 2006 ; Lindsay and Middleton 2012 onwards; Xing et al 2013 ; Fraser-Jenkins et al 2018 ), as well as an unidentified taxon which was labelled as “ Tectaria sp.1” by Dong et al (2018a) . Of these species, the most contentious species are T. subfuscipes and T. subsageniacea .…”
Section: Introductionmentioning
confidence: 99%
“…Kuo and T. subsageniacea (Christ) Christenh. ( Holttum 1988 ; Kuo 1997 ; Zink 2006 ; Lindsay and Middleton 2012 onwards; Xing et al 2013 ; Fraser-Jenkins et al 2018 ), as well as an unidentified taxon which was labelled as “ Tectaria sp.1” by Dong et al (2018a) . Of these species, the most contentious species are T. subfuscipes and T. subsageniacea .…”
Section: Introductionmentioning
confidence: 99%
“…By examining specimens of all Tectaria species with 1-pinnate, pinnae-entire fronds recorded in Indochina and nearby regions ( Tardieu-Blot and Christensen 1941 ; Tagawa and Iwatsuki 1988 ; Xing et al 2013 ; Fraser-Jenkins et al 2018 ), we found that some specimens of T. danangensis look very like those of T. fissa (Kunze) Holttum, a species frequently occurring in western Malesia but not in Indochina ( Holttum 1991 ; Lindsay and Middleton 2012 onwards ). A detailed comparison (Table 1 ) showed that T. danangensis differs from T. fissa and other species having 1-pinnate fronds by its venation lacking distinct transverse veins between lateral veins and its sori being generally in only two rows (versus 4–6 rows) between lateral veins.…”
Section: Discussionmentioning
confidence: 89%
“…For additional synonymy see Moran (1995), Mickel & Smith (2004), Navarrete & Øllgaard (2000), Yan & al. (2013), Fraser-Jenkins & al. (2017, Schwartsburd & al.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Species estimates vary widely, from 33 (Moore, 2010) to 60 (PPG-I, 2016), or 100 (Yuan & al., 2012). Important regional treatments include Cambodia (Sun, 2014), China (Yan & al., 2013), India (Fraser-Jenkins & al., 2017), Japan (Nakaike, 1975), Nepal (Fraser-Jenkins & al., 2015), Taiwan (Knapp, 2011;TPG, 2019TPG, , 2021, and Thailand (Tagawa & Iwatsuki, 1979). We include 44 species and 4 named hybrids here based upon molecular phylogenetic and morphological evidence.…”
Section: ■ Discussionmentioning
confidence: 99%